1998
DOI: 10.1097/00006534-199807000-00035
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Effects of Ultrasound-Assisted Lipoplasty

Abstract: The objective of our study was to investigate the effects of ultrasonic energy on tissues, using a porcine model, performed under various instrumental and procedural parameters. Domestic pigs were anesthetized and prepared for surgery. An incision was made on the side of the hip randomly assigned to the right or left side. Tumescence solution was infiltrated via a blunt tip, small diameter cannula, followed by performance of standard liposuction. On the contralateral side, a similar incision was made. For ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…16,17 At the same time, investigations by Karmo et al and Kenkel et al have demonstrated that comparable, if not reduced, levels of blood loss result from ultrasound-assisted lipoaspiration relative to suction-assisted lipoaspiration. 18,19 In addition to these patient benefits, progress in the conduct of lipoaspiration arising from technical refinements in ultrasound-assisted lipoaspiration equipment have been reported by operating surgeons. 14,16 However, the technique is not without its drawbacks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 At the same time, investigations by Karmo et al and Kenkel et al have demonstrated that comparable, if not reduced, levels of blood loss result from ultrasound-assisted lipoaspiration relative to suction-assisted lipoaspiration. 18,19 In addition to these patient benefits, progress in the conduct of lipoaspiration arising from technical refinements in ultrasound-assisted lipoaspiration equipment have been reported by operating surgeons. 14,16 However, the technique is not without its drawbacks.…”
mentioning
confidence: 99%
“…The panel's findings, and those of other investigators, established that concern over long-term tissue effects arising from the above factors is unfounded. 19,21,23 The true benefits appreciated by patients treated with ultrasound-assisted lipoaspiration compared with alternative lipoplasty techniques remain to be elucidated. However, the adaptation of ultrasoundassisted lipoaspiration in the clinical arena is expanding at an exponential rate.…”
mentioning
confidence: 99%
“…Tissue coagulation with necrosis is a usual finding after electrosurgical or ultrasonic tissue dissection. Ultrasoundassisted liposuction induces fat liquefaction and in the remaining adipose tissue margin, fat necrosis [17]. Although the use of water irrigation for UAL helps to reduce tissue heat, an increase in tissue temperature is expected.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 The possibility of SL and FR production resulting from UAL has been Sonochemistry and Sonoluminescence in Simulated Ultrasound-assisted Lipoplasty Environment S c i e n t i f i c F o r u m rejected by others. 14,15 Low-intensity SL emission was detected in our laboratory by a sensitive photon-detecting system in the process of sonication of wetting solution and varying ratios of FFP, at conditions simulating intercellular environment and UAL operating conditions in the frequency and intensity range used in current instrumentation. SL emission is multifactorially dependent.…”
Section: Discussionmentioning
confidence: 99%